Pengaruh Penggunaan Model Case Based Learning (CBL) Terhadap Pemecahan Masalah Pada Pembelajaran IPAS Siswa Kelas IV SD - Fidia, Salsabila Nurul; Ariani, Farida; Amris, Firda Khairati; Septiani, Liza (Institut Agama Islam Sumatera Barat, 2024)
This research is supported by observational data which shows, firstly, students lack sharp thinking skills, logical analysis skills, the ability to recognize general patterns and the ability to synthesize the concepts being taught to draw conclusions, this is because students find it difficult to complete the questions given and the difficulty in combining the calculation results with existing symptoms. Second, the lack of information deepens students' knowledge about the science subjects they are studying, this is because science subjects are often considered difficult to study because a lot of the material requires reasoning, understanding and memorization. Third, students' science and science literacy skills are still low, this is due to the weak learning model used. Fourth, it is difficult for students to apply the science and science learning model, this is because the science and science learning model does not attract students' interest. In this case, to respond, the researcher conducted research aimed at finding out the effect of using the Case Based Learning (CBL) model on problem solving in science and science learning for fourth grade students at SD Negeri 01 Pauh Kurai Taji. The method used in this research is quantitative with a one group pretestposttest design. The target population in this study was class IV students at SD Negeri 01 Pauh Kurai Taji with a sample of 22 people in this study. Data collection techniques in this research, the author uses a questionnaire instrument (questionnaire). Meanwhile, the data analysis techniques used in this research are normality test, homogeneity test and hypothesis test. The results of the research show that the use of the Case Based Learning (CBL) model has an influence on problem solving in science and science learning for class IV students at SD Negeri 01 Pauh Kurai Taji. This conclusion was obtained based on the T-test results, it was found that the questionnaire value was 64.523 > 2.079, meaning t count > t table and the T-test question value was 30.397 > 2.079 which showed t count > t table. So this shows that H0 is rejected and Ha is accepted, meaning: there is an influence of the use of the Case Based Learning (CBL) model on problem solving in science and science learning for class IV students at SD Negeri 01 Pauh Kurai Taji.